2021
DOI: 10.3390/su132111771
|View full text |Cite
|
Sign up to set email alerts
|

Re-Use of Silico-Manganese Slag

Abstract: The world’s rapidly growing demand for raw manganese has made it increasingly important to develop methods for the economic recovery of manganese from secondary sources. The current study aims to present possible ways for the recycling and reuse of silico-manganese slag landfilled in Tulcea, City on the Danube River close to the Danube Delta Biosphere Reserve in order to save the natural resources raw of manganese. In the last three decades, the ferroalloy production plant has over 2.6 million tons of slag. Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Waste materials, for instance, from heavy or construction industries, are a major environmental problem, presenting a threat to the environment [3][4][5][6]. However, as previously stated, industrial waste can be an interesting source of valuable compounds, such as manganese obtained from silico-manganese waste slag [7], magnesium from industrial effluents [8], or rare earth metals from secondary sources, such as coal ash, red mud, or phosphogypsum [9]. Another important example is the reuse of sources of calcium.…”
Section: Introductionmentioning
confidence: 99%
“…Waste materials, for instance, from heavy or construction industries, are a major environmental problem, presenting a threat to the environment [3][4][5][6]. However, as previously stated, industrial waste can be an interesting source of valuable compounds, such as manganese obtained from silico-manganese waste slag [7], magnesium from industrial effluents [8], or rare earth metals from secondary sources, such as coal ash, red mud, or phosphogypsum [9]. Another important example is the reuse of sources of calcium.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, catalysts based on Co and Mn have garnered attention for their high bifunctional efficacy in ORR and OER. This largely ascribes to the high oxidation potential of Co and the enhanced electronic transport characteristics of Mn [27][28][29]. Nonetheless, the inherently low electronic conductivity of these mixed valence transition metal oxides remains a critical barrier, impeding further enhancements in catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that increasing the Si concentration reduces thermal expansion and can be employed as a hard phase for improving the alloy's wear resistance [29]. Furthermore, some research studies have investigated the importance of various phases on mechanical and corrosion properties [30,31].…”
Section: Introductionmentioning
confidence: 99%